The relationship between urinary tract infections and preterm labor for pregnant women in Syria - Sayyoh, Mais Ahmed; Hasan, Louai Ibrahim; Al-dali, Issam Mohammad (Journal of medical and pharmaceutical sciences, 2022)
Objective: The aim of this study is to determine the prevalence of urinary tract infection (UTI) in pregnant women with preterm labor. In addition to, estimating the association between UTI and occurrence of preterm labor. Patients and Methods: Descriptive Case- Control Study conducted for the period one year (June 2020 –June 2021) at Tishreen University Hospital in Lattakia- Syria. The study included 125 pregnant women without risk factors for preterm labor who were divided into case group (70): with preterm labor, and control group (55) with full term labor. Investigations for presence of UTI were performed in two groups. Results: The mean age was 25.5±5.3 years in the case group and 26.2±4.89 years in control group without significant difference. Previous history of preterm labor was more frequently in case group (17.5% vs.2.7%, p: 0.03). E.COLI was more frequently in the two groups. It was found that 16 patients (22.8%) in the case group and 4 patients (7.3%) in the control group had UTI with significant difference (p<0.05). In the multivariate regression model, UTI was significantly associated with preterm labor (OR: 3.7[1.18- 12.05], P: 0.02. Conclusion: UTI is associated with the risk of preterm labor. Therefore, early detection and treatment of the infection can reduce effectively the risk of preterm labor.